Electron Microscopic Visualization of Sites of Nascent DNA Synthesis by Streptavidin-Gold Binding to Biotinylated Nucleotides Incorporated in Vivo - Hiriyanna, K. T.; Varkey, J.; Beer, M.; Benbow, R. M. (The Journal of cell biology, 1988)
Biotinylated nucleotides (bio-11-dCTP, bio-11-dUTP, and bio-7-dATP) were microinjected into unfertilized and fertilized Xenopus laevis eggs. The amounts introduced were comparable to in vivo deoxynucleoside triphosphate pools. At various times after microinjection, DNA was extracted from eggs or embryos and subjected to electrophoresis on agarose gels. Newly synthesized biotinylated DNA was analyzed by Southern transfer and visualized using either the BluGENE or Detek-hrp streptavidin-based nucleic acid detection systems. Quantitation of the amount of biotinylated DNA observed at various times showed that the microinjected biotinylated nucleotides were efficiently incorporated in vivo, both into replicating endogenous chromosomal DNA and into replicating microinjected exogenous plasmid DNA. At least one biotinylated nucleotide could be incorporated in vivo for every eight nucleotides of DNA synthesized. Control experiments also showed that heavily biotinylated DNA was not subject to detectable DNA repair during early embryogenesis (for at least 5 h after activation of the eggs). The incorporated biotinylated nucleotides were visualized by electron microscopy by using streptavidin-colloidal gold or streptavidin-ferritin conjugates to bind specifically to the biotin groups projecting from the newly replicated DNA. The incorporated biotinylated nucleotides were thus made visible as electron-dense spots on the underlying DNA molecules. Biotinylated nucleotides separated by 20-50 bases could be resolved. We conclude that nascent DNA synthesized in vivo in Xenopus laevis eggs can be visualized efficiently and specifically using the techniques described.